Currency war Next Crisis - Ghezail, Mohamed Mouloud; Sari, Ali (Dirassat Journal Economic Issue, 2016)
the currency global exchange rates has Become one of the economic channel collision and inconsistency between the major industrialized countries, where that countries interfere in the exchange rates values by money ways, in order to influence some of the economic indicators, such as some current account and trade balance, indebtedness, and the values ​​of assets and other indicators. In but when the governments allows of the competition in the field of exchange rates by lowering interest rates, or to change the names of the tax, or the application of fiscal policies to reduce the value of their currencies, or quantitative easing to offer her money, so the war of currency will have no end. The result may be flammable wars, protectionism, such as those caused the Great Depression in the thirties of the last century, and the dollar fell a lot, and the euro rose considerably, while the yen rose too much also dropped the Yuan overly so, these indicators suggest the beginning of a currency war may be crisis the next.